BERBERINE HYDROCHLORIDE COULD PROVE TO BE A PROMISING BULLET AGAINST CLOSTRIDIUM DIFFICILE INFECTION: A PRELIMINARY STUDY FROM SOUTH INDIA - Chakraborty, Rituparna; Lobo, Richard; Prabhu, Mukhyaprana M; Umakanth, Shashikiran; Chowdhury, Goutam; Mukhopadhyay, Asish K; T, RAMAMURTHY; Ballal, Mamatha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Recurrent Clostridium difficile infection (CDI) and the emergence of strains with reduced susceptibility to metronidazole and vancomycin warrants alternative therapy. Hence, we tested the potential efficacy of the natural compound berberine hydrochloride (BBRHCl) against toxigenic C. difficile. Methods: Three representative polymerase chain reaction confirmed, toxin-positive strains were included in the study. Pulsed-field gel electrophoresis (PFGE) profile and antibiogram of the strains were analyzed along with 10 other toxin positive isolates. Efficacy of BBRHCl against toxigenic C. difficile was determined using agar diffusion by punch well method. Results: PFGE grouped the test strains into three clusters with unique susceptibility pattern toward standard antibiotics. BBRHCl was efficacious against the test strains at a concentration ranging between 6.25 Î¼g/ml and 10 mg/ml. BBRHCl's breakpoint point inhibitory zone diameter was equivalent (p<0.001) to the epidemiological cutoff values for teicoplanin, vancomycin and 2% black seed oil. Although the predicted concentration of BBRHCl for breakpoint zone diameter equivalent to European Committee on Antimicrobial Susceptibility Testing's epidemiological cutoff value for metronidazole was observed to fall outside the tested concentration range; it was still within the safe dosage for humans. Conclusion: The present study is promising in considering BBRHCl as a potent substitute or adjunct not only for metronidazole, vancomycin and teicoplanin but also for natural compounds like 2% black seed oil for managing resistant cases of CDI. Owing to BBRHCl's direct antibacterial and antiinflammatory action, further investigations will aid in the proper characterization of the therapeutic effects of similar plant compounds, to develop safe and effective drugs against the epidemiological outbreak of CDI.